152. Protective Antibody Levels 7.5 Years After Primary Vaccination in Adolescence With a Recombinant, 4-Component, Meningococcal Serogroup B Vaccine (4CMenB) and Response to a Booster Dose in Adolescents and Young Adults: Phase IIIb Clinical Findings. (26th November 2018) - Nolan, Terry; O'Ryan, Miguel; Santolaya, María Elena; De Looze, Ferdinandus; Marshall, Helen; Richmond, Peter; Henein, Sam; Rheault, Paul; Heaton, Ken; Perrett, Kirsten; Garfield, Hartley; Gupta, Anil; et al.
Abstract: Background: 4CMenB has been shown to be immunogenic with an acceptable safety profile in infants and young adolescents. However, no data on long-term persistence after primary vaccination in adolescents are available. This is the first study to assess antibody persistence, booster response, and safety of 4CMenB in adolescents and young adults up to 7.5 years following the primary vaccination in adolescence. Methods: This phase 3b, open-label, extension study (NCT02446743) assessed the antibody persistence and booster response at 4 years (Canada and Australia, NCT01423084) or 7.5 years (Chile, NCT00661713) after primary vaccination with 4CMenB (following 0 + 1-, 0 + 2-, or 0 + 6-month schedules), compared with vaccine-naïve (VN), healthy controls. Chilean follow-on (FO) and VN participants aged 18–24 years received either a booster dose of 4CMenB 7.5 years postprimary series (Group FO, N = 131) or 2 primary doses, 1 month apart (Group VN, N = 150). Immunogenicity was measured using human serum bactericidal antibody assay (hSBA) against antigen-specific strains. Immune response was evaluated 1 month post-booster vaccination and compared with VN controls at 1 month post-first dose. Kinetics of antibody responses were measured at 3, 7, and 30 days post-vaccination. Safety was assessed. Results: Antibody levels waned at 7.5 years postprimary vaccination in Group FO, but were higher than in Group VN at baseline, for all antigens except NHBA (table). At 1 month post-booster/post-first dose, 93–100% (Group FO) and 62–93% (Group VN) of participants had hSBA titres ≥4; GMTs ranged between 41 and 1, 951 (Group FO) and 9.43–46 (Group VN) (table). The percentages of FO participants with hSBA titres ≥4 remained similar to prebooster for all 4 antigens at 3 days, increased at 7 days, and remained unchanged or increased further 30 days post-booster. The reactogenicity of 4CMenB was consistent with previous observations in this age group; no safety concerns were identified during the study. Conclusion: Antibody levels in adolescents and young adults declined at 7.5 years after a 2-dose primary series of 4CMenB, but were higher than baseline levels in VN controls. An additional dose of 4CMenB elicited strong anamnestic responses—substantially higher than 1 dose in VN controls. Funding: GlaxoSmithKline Biologicals SA. Disclosures: T. Nolan, GSK: Research Contractor and Scientific Advisor, Research grant. Pfizer: Research Contractor, Research grant. M. O'Ryan, GSK: Investigator, Research support. F. De Looze, GSK: Investigator and Research Contractor, Research grant and Research support. H. Marshall, Pfizer: Grant Investigator and Investigator, Research grant. GSK: Grant Investigator and Investigator, Research grant. P. Richmond, GSK: Grant Investigator and Scientific Advisor, Grant recipient. S. Henein, SKDS Research Inc.: Investigator, Research payment. K. Heaton, Devonshire Clinical Research Inc.: Investigator, Research payment. M. Ferguson, GSK: Investigator, Salary from independent research clinic, CRG. D. D'Agostino, GSK: Employee, Salary. D. Toneatto, GSK: Employee and Shareholder, Salary.